A survey of cytomegalovirus (CMV) DNA in primary sclerosing cholangitis (PSC) liver tissues using a sensitive polymerase chain reaction (PCR) based assay. - Mehal, W; Hattersley, A; Chapman, R; Fleming, K (1992)
Reactivation of cytomegalovirus (CMV) has been implicated as a possible etiological agent in primary sclerosing cholangitis (PSC) partly because of the ability of CMV infection to cause hepatobiliary damage, and further because of the recent recognition of a PSC-like syndrome in AIDS patients, many of whom have hepatobiliary infection with CMV. Direct evidence of CMV infection in PSC has come from a study detecting CMV DNA in 7/7 PSC livers, but only 5/20 controls. We have developed an assay for CMV-DNA by amplification of the immediate early region of CMV using the polymerase chain reaction, followed by Southern blotting and 32P oligoprobing of the amplification product. This system has an average sensitivity of at least 25 copies of CMV-DNA per 5000 formalin-fixed paraffin-embedded cells. 37 PSC and 19 control samples of formalin-fixed paraffin-embedded hepatobiliary tissues were studied. Amplification for the beta-globin in each sample was used as an amplification control, and fetal lung with known CMV infection as the CMV-positive control. 37/37 PSC tissues amplified for beta-globin, and one of these was positive for CMV-DNA. All 19 controls amplified for beta-globin, with none being positive for CMV. The lack of CMV-DNA in 35/36 PSC samples at a level of 25 copies per 5000 cells, we believe, rules out any significant CMV reactivation in these tissues, and suggests that CMV replication and re-activation is not responsible for the progression of PSC.